2022
DOI: 10.3390/ijerph19052590
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment for the Residential Area Adjacent to a Former Chemical Plant

Abstract: A health risk assessment was carried out for the residents of Łęgnowo-Wieś settlement adjacent to a former Zachem Chemical Plant, Bydgoszcz, Poland. Due to the unique Zachem site history and contamination profile, an innovative strategy for soil sampling and contaminant selection was applied. The novelty in the developed strategy consisted of selecting substances for the health risk assessment, taking into consideration the location and boundaries of the groundwater contamination plumes in relation to contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…High CCR is found in the areas where IwWQI suggests poor/very poor groundwater, with Pb being the chief risk mainly in the eastern part, in areas with intensive vegetable growing, while Ni is the chief risk along the Dâmboviţa River and in the south of Târgovişte municipality. This pattern is also mentioned in other studies [ 40 , 89 ] in which high values of carcinogenic elements are found along the main hydrographic channels and increase from upstream to downstream.…”
Section: Resultssupporting
confidence: 85%
“…High CCR is found in the areas where IwWQI suggests poor/very poor groundwater, with Pb being the chief risk mainly in the eastern part, in areas with intensive vegetable growing, while Ni is the chief risk along the Dâmboviţa River and in the south of Târgovişte municipality. This pattern is also mentioned in other studies [ 40 , 89 ] in which high values of carcinogenic elements are found along the main hydrographic channels and increase from upstream to downstream.…”
Section: Resultssupporting
confidence: 85%
“…A large number of articles focused on assessing human health risks in sites contaminated with PTEs due to various industrial activities has recently been published. Examples of this include the works of Wu et al [6], Gruszecka-Kosowska et al [7], Xia et al [8], Custodio et al [9], Wcislo [10], Wcislo and Bronder [11], Wcislo et al [12], and Wu et al [13]. These publications summarise the research on the dangers that heavy metal contamination poses to human health in a variety of environmental contexts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in groundwater in China, and given its stability, it can easily migrate to rivers and other aquatic sources to cause significant pollution [5]. Of particular concern are abandoned NB contaminated sites that can continue to pollute the surrounding environment, and it is estimated that some 2.8 million contaminated sites may exist in Europe [6]. NB can cause serious health problems, such as shortness of breath, vomiting, and nausea [7,8].…”
Section: Introductionmentioning
confidence: 99%